2013
DOI: 10.1371/journal.pone.0077537
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of KLF2 Modulation on the Transcriptional Program and Function of CD8 T Cells

Abstract: Krüppel-like factor 2 (KLF2) is a transcription factor that is highly expressed in quiescent T lymphocytes and downregulated in effector T cells. We now show that antigen receptor engagement downregulates KLF2 expression in a graded response determined by the affinity of T cell antigen receptor (TCR) ligand and the integrated activation of protein kinase B and the MAP kinases ERK1/2. The present study explores the importance of KLF2 downregulation and reveals that the loss of KLF2 controls a select portion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 44 publications
4
33
1
Order By: Relevance
“…KLF2, a downstream transcription factor of MEF2A (Kumar et al, ), could up‐regulate miR‐143 expression in endothelial cells (Hergenreider et al, ), and p‐AKT expression was opposite to KLF2 (Preston et al, ), suggesting that miR‐143 expression may be regulated by MEF2A. Consistently, our results have shown that up‐regulation of MEF2A promoted miR‐143 expression, which was inhibited by the KLF2 knockdown.…”
Section: Discussionsupporting
confidence: 88%
“…KLF2, a downstream transcription factor of MEF2A (Kumar et al, ), could up‐regulate miR‐143 expression in endothelial cells (Hergenreider et al, ), and p‐AKT expression was opposite to KLF2 (Preston et al, ), suggesting that miR‐143 expression may be regulated by MEF2A. Consistently, our results have shown that up‐regulation of MEF2A promoted miR‐143 expression, which was inhibited by the KLF2 knockdown.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, overexpression of Klf2 lead to dramatic changes in expression of a broad range of genes related to trafficking, effector function, cytokine receptors, and transcriptional regulation [48]. Therefore, we next asked whether IL-15 complexes could alter effector functions of memory CD8 T cells.…”
Section: Resultsmentioning
confidence: 99%
“…This pattern of localization correlated well with decreased CD69 and increased S1P1 expression patterns in Q4- and T4-primed cells as compared with N4-primed cells. Recent in vitro studies have shown that CXCR3 expression is rapidly induced on CD8 + T cells during primary stimulation in a pMHC affinity–dependent manner (Preston et al, 2013). We show that, also in vivo, N4-primed OT-I T cells showed the highest CXCR3 expression and moved to the outer cortical regions of LNs in a CXCR3-dependent manner, although in our hands, we were unable to detect CXCL9 or CXCL10 in LN sections (unpublished data).…”
Section: Discussionmentioning
confidence: 99%